Very-Brief, Web-Based Interventions for Reducing Alcohol Use and Related Problems among College Students: A Review - Leeman, Robert F.; Perez, Elliottnell; Nogueira, Christine; DeMartini, Kelly S. (Frontiers in Psychiatry, 2015)
Very brief, web-based alcohol interventions have great potential due to their convenience, ease of dissemination, and college students’ stated preference for this intervention modality. To address the efficacy of these interventions, we conducted a review of the literature to identify randomized, controlled trials (RCTs). Fifteen published reports were included. All RCTs meeting criteria for inclusion tested an intervention that featured personalized feedback on students’ patterns of alcohol consumption. This review found some evidence to support the efficacy of very brief, web-based interventions among college students for alcohol use reduction. Several trials, however, reported no evidence of efficacy and it is possible that methodological limitations of some of the studies could have had an impact on their results. This review did not yield evidence to support the efficacy of very-brief, web-based interventions for reduction of alcohol-related problems among college students. We found evidence to support the efficacy of two main types of intervention content: (a) focused solely on personalized normative feedback designed to correct misconceptions about peer alcohol consumption and (b) multi-component interventions. Future research is needed to test enhancements to very brief, web-based interventions that feature personalized feedback on patterns of alcohol use and to determine for which types of college drinkers (e.g., heavier or lighter drinkers) these interventions are most efficacious. In addition, future studies are needed to test novel, very brief, web-based interventions featuring approaches other than personalized feedback. In summary, this review yielded some evidence supporting very brief, web-based interventions in reducing alcohol use but not related problems in college students. Very brief, web-based interventions are worth pursuing given their convenience, privacy and potential public health benefit.